Philippine encyclopedia of the social sciences - Salita, Domingo C. (Philippine Social Science Council, 1993)
For the promotion of education, the Philippine Encyclopedia of the Social Sciences is published consisting of five volumes arranged by discipline. Due to some circumstances, the general reference section only acquires two volumes covering the discipline of history which attempts to give a portrayal of the state of the art social sciences in the Philippines today. Volume I discusses the definition and characteristic while Volume II presents the development and advancement of history and historians.